“Nel paese del Gattopardo”. Gustaw Herling‑Grudziński e Giuseppe Tomasi di Lampedusa - Śniedziewka, Magdalena (Romanica Silesiana)
The present work is devoted to the problem of reception of the Sicilian literature in the Gustaw Herling‑Grudziński’s œuvre. The article is an analysis of the Herling‑Grudziński’s essay on The Leopard published in 1959 in “Kultura”. Herling in his work analyzes the crucial problem of the sicilianity (sicilianità) and the obsession with death. In the Journal Written at Night and in the essay about Lampedusa Grudziński “rewrites” the vision of Sicily and diagnoses the problem of insularity (insularità). Key words: Gustaw Herling‑Grudziński, Giuseppe Tomasi di Lampedusa, Sicily, The Leopard, insularity